ANALISIS PERFORMANSI SUPPLY CHAIN PADA PRODUK SEPATU FLAT SHOES MENGGUNAKAN MODEL SCOR - Fathoni, M Yoka; Nishom, M; Wibowo, Dega Surono (Jurnal Informatika: Jurnal Pengembangan IT, 2023)
The performance measure of a service cannot be in form and does not result in ownership. Service itself is a form of activity carried out by one or more people, and also is agility (intangible and affected by previous sales). So the services purchased by customers cannot be counted, measured or stored to determine the quality of their services. One of the shoe sales industries is Toko XYZ, this shoe store is one of the largest brands in the archipelago. The prices offered on the national and international market are quite cheap. In order to improve a strategy so that many consumers visit XYZ shoe stores, and for XYZ it is possible to achieve the expected targets with integrated marketing. Data collection in this study consists of 2 steps, namely preparation, this stage is carried out before conducting research such as looking for references on the internet, theoretical foundations that support research such as SCOR model theory and journals. Furthermore, with the contents of the questionnaire compiled to represent the dimensions of service performance quality. The conclusion of the study is that the statement attributes expected by the customer through the SCOR Model method are positive.